Combinatorial optimization and metaheuristic algorithms - بن علي, عبد الكامل (University of Eloued جامعة الوادي, 2024)
مرحبًا بكم في المنهج الدراسي لمقرر "تحسين التوافقي والخوارزميات الميتا-استكشافية". يهدف هذا المقرر إلى تزويد الطلاب بفهم شامل للمبادئ والتقنيات والتطبيقات المتعلقة بتحسين التوافقي والخوارزميات الميتا-استكشافية. تظهر مشكلات تحسين التوافقي (COPs) في العديد من السيناريوهات الواقعية حيث يكون الهدف هو العثور على أفضل ترتيب أو تركيب لعناصر من مجموعة محدودة. غالبًا ما تكون هذه المشكلات صعبة بسبب تعقيدها الذاتي والنمو الأسي للحلول المحتملة. توفر الخوارزميات الميتا-استكشافية استراتيجيات قوية لحل مشكلات تحسين التوافقي بكفاءة. من خلال استكشاف الخوارزميات القائمة على الحل الفردي والخوارزميات القائمة على المجموعات، سيتعلم الطلاب أساليب متنوعة للتعامل مع تحديات التحسين المختلفة. بالإضافة إلى ذلك، سنغوص في موضوع التحسين متعدد الأهداف، حيث يكون الهدف تحسين أهداف متعارضة متعددة في الوقت ذاته. على مدار هذا المقرر، لن يكتسب الطلاب المعرفة النظرية فقط، بل سيكتسبون أيضًا خبرة عملية من خلال تنفيذ وتحليل الخوارزميات الميتا-استكشافية عمليًا. بنهاية المقرر، سيكون الطلاب مجهزين بمهارات قيمة تمكنهم من مواجهة مشكلات تحسين توافقي معقدة والمساهمة في التطورات في مختلف المجالات. آمل أن يكون هذا المنهج بمثابة دليل لرحلتكم التعليمية وأن يلهمكم لاستكشاف العالم الرائع للتحسين التوافقي والخوارزميات الميتا-استكشافية. أطيب التمنيات بتجربة تعليمية مثمرة وممتعة!Welcome to the syllabus for the course "Combinatorial Optimization and Metaheuristic Algorithms". This course aims to provide students with a comprehensive understanding of the principles, techniques, and applications of combinatorial optimization and metaheuristic algorithms. Combinatorial optimization problems (COPs) arise in various real-world scenarios where the goal is to find the best arrangement or combination of elements from a finite set. These problems are often challenging due to their inherent complexity and the exponential growth of possible solutions. Metaheuristic algorithms offer powerful strategies for solving COPs efficiently. By exploring both single-solution based and population-based metaheuristics, students will learn versatile approaches to address diverse optimization challenges. Furthermore, we will delve into multi-objective optimization, where the goal is to optimize multiple conflicting objectives simultaneously. Throughout this course, students will not only gain theoretical knowledge but also practical experience through hands-on implementation and analysis of metaheuristics. By the end of the course, students will be equipped with valuable skills to tackle complex COPs and contribute to advancements in various domains. I hope this syllabus serves as a guide to your learning journey and inspires you to explore the fascinating world of combinatorial optimization and metaheuristics. Best wishes for a rewarding and enriching learning experience!
مطبوعة بيداغوجية لطلبة سنة أولى ماستر اعلام آلي تخصص الذكاء الإصطناعي و علم البيانات
Keywords: تحسين التوافقي; الخوارزميات الميتا-استكشافية; مشكلات متعددة الأهداف; Combinatorial Optimization; Metaheuristic Algorithms; Multi-objective Problems; Solution Space Exploration